Gambaran Perilaku Komunikasi Guru Sekolah Menengah Pertama berdasarkan Konstruk Teacher Communication Behaviour Questionnaire (TCBQ) - Suprawati, M.M Nimas Eki; Savira, Alice Whita; Rosita, Febriana Ndaru (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2023)
This study aims to describe communication behavior of Indonesian junior high school teachers based on the construct of the Teacher Communication Behavior Questionnaire (TCBQ). It was conducted in response to the need to develop teacher communication measurement with a clear construct to improve the quality of teacher communication research in Indonesia. Culture plays an important role in affecting communication behavior. It is necessary to study whether TCBQ's constructs are also found in teacher communication in Indonesia. Teacher communication behavior is important for learning, especially for students in early adolescence. This research used qualitative descriptive. Eleven junior high school teachers participated in this study using naturalistic observation obtained through video recording in the classroom. The results showed that according to the TCBQ perspective, participants perform four types of communication behavior: (1) challenging; (2) encouraging-praise; (3) understanding-friendly; and (4) controlling.